Islamic Appraisal of Tribal Politics Among Muslims in Taraba State - Abdulmumini Bawuro Manga; Abdulwahab AbdulQadir Ibrahim; Aminu Muallimu Kambari (Jurnal EL-QANUNIY: Jurnal Ilmu-Ilmu Kesyariahan dan Pranata Sosial, 2026)
Taraba state, Nigeria, is characterized by ethnic and religious diversity, with Islam playing a major role in its socio-political history. However, the emergence of tribal politics among Muslims has posed serious challenges to unity, political participation and socio-economic development. This paper appraises tribal politics among Muslims in Taraba state from an Islamic perspective. It analyzes the causes, manifestations and the results of tribalism and evaluates them against Islamic teachings on unity, justice, and brotherhood. The study adopts qualitative methodology, using Qur’anic teachings, Hadith literature, interviews and participatory observations as its primary source of data, and scholarly documents, like thesis, journals, textbooks radio productions among others as the its secondary source of data. Findings reveals that tribalism contradicts Islamic principles and contributes to political marginalization and internal disunity. The study also, found that, relations among Muslims were relatively cordial before and shortly after the creation of Taraba state in 1991, but later deteriorated with the return of democratic politics, leadership contest, and rising ethnic sentiments, while noting that from around year 2000 onward, integrative determinants such as intermarriages, Islamic educational institutions and shared commercial activities have helped rebuild unity. The study recommends promoting unity among Muslims, through intermarriages, tolerance, merit-based politics guided by Islamic principles, continues scholarly engagement on Qur’anic and Prophetic traditions teachings against tribalism, institutionalized inter-ethnic dialogue, and the establishment of forums and empowerment initiatives such as zakat and waqf to support especially youths